2017
DOI: 10.1128/mbio.01979-17
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CytosolicShigella flexnerivia a C-Terminal Triple-Arginine Motif of GBP1 Inhibits Actin-Based Motility

Abstract: Dynamin-like guanylate binding proteins (GBPs) are gamma interferon (IFN-γ)-inducible host defense proteins that can associate with cytosol-invading bacterial pathogens. Mouse GBPs promote the lytic destruction of targeted bacteria in the host cell cytosol, but the antimicrobial function of human GBPs and the mechanism by which these proteins associate with cytosolic bacteria are poorly understood. Here, we demonstrate that human GBP1 is unique among the seven human GBP paralogs in its ability to associate wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
208
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(232 citation statements)
references
References 57 publications
(77 reference statements)
24
208
0
Order By: Relevance
“…In the absence of SdhA, the LCV becomes disrupted and L. pneumophila is detected in the cytoplasm of the infected macrophage (Creasey & Isberg, 2012;Laguna et al, 2006). Bacteria exposed in this fashion to the cytosol are susceptible to recruitment of the interferon-regulated guanylate-binding proteins (GBP) family of anti-microbial proteins, resulting in leakage of lipopolysaccharide (LPS) and activation of caspase-11 (Creasey & Isberg, 2012;Liu et al, 2018;Piro et al, 2017). As a consequence, gasdermin D is activated and pyroptotic cell death ensues (Aachoui et al, 2013;Pilla et al, 2014;Shi et al, 2015).…”
mentioning
confidence: 99%
“…In the absence of SdhA, the LCV becomes disrupted and L. pneumophila is detected in the cytoplasm of the infected macrophage (Creasey & Isberg, 2012;Laguna et al, 2006). Bacteria exposed in this fashion to the cytosol are susceptible to recruitment of the interferon-regulated guanylate-binding proteins (GBP) family of anti-microbial proteins, resulting in leakage of lipopolysaccharide (LPS) and activation of caspase-11 (Creasey & Isberg, 2012;Liu et al, 2018;Piro et al, 2017). As a consequence, gasdermin D is activated and pyroptotic cell death ensues (Aachoui et al, 2013;Pilla et al, 2014;Shi et al, 2015).…”
mentioning
confidence: 99%
“…Furthermore, it was found that IpaH9.8 synthesises a ubiquitin-coat on S. flexneri, which in contrast to the host-generated ubiquitin coat does not have antimicrobial effects on the cytosolic bacteria but rather supports the pathogen, possibly through antagonising GBP recruitment (Wandel et al, 2017). All in all, these studies point out that targeting of GBPs by IpaH9.8 is a prerequisite for S. flexneri to counteract restriction of replication and suppress GBP-mediated immunity (Li et al, 2017;Piro et al, 2017;Wandel et al, 2017).…”
Section: Unlike the Previously Described Immunomodulatory Functions Ofmentioning
confidence: 89%
“…Poly-ubiquitinylation of NEMO leads to its degradation in a proteasome-dependent manner, thereby dampening NF-κB activation (Ashida et al, 2010). Recently, several independent studies found that IpaH9.8 is implicated in IFN-induced antimicrobial defences and counteracts cell-autonomous immunity mediated by the family of GBPs (guanylate-binding proteins; Li et al, 2017;Piro et al, 2017;Wandel et al, 2017). Upon invasion into human IFNγ-activated cells, S. flexneri is initially targeted by human GBP1 (hGBP1), which recognises cytosol-invading Gram-negative bacteria via the LPS O-antigen and then promotes the hierarchical recruitment of additional GBP paralogs.…”
Section: Unlike the Previously Described Immunomodulatory Functions Ofmentioning
confidence: 99%
“…Also a coiled-coil interface between hGBP-1 and hGBP-5 might be interesting when recalling the recently published study in which a triple arginine motif in the polybasic region (located at the end of the GED) is responsible for the specific targeting of hGBP-1 to S. flexneri [12]. The isoform hGBP-5 was not under the hGBPs guided to S. flexneri by hGBP-1 and some fraction of hGBP-1 seems to reside in the cytoplasm [11][12][13]. One could speculate that hGBP-5 might inhibit hGBP-1 from targeting the bacterium by forming a coiled-coil interface during hetero interaction and thus blocking the triple arginine motif in…”
Section: Coiled-coil Interaction Can Explain the Different Dissociatimentioning
confidence: 95%
“…The hGBPs exhibit diverse biological functions which mark them as key players in the innate immune response [6][7][8][9][10]. Most recently, it was demonstrated that hGBP-1 prevents cell-to-cell spread of Shigella flexneri by inhibiting the actin-dependent motility of the gram-negative bacterium [11,12]. Interestingly, the bacterium evolved a mechanism to counteract this host defence [11][12][13].…”
Section: Introductionmentioning
confidence: 99%